2014
DOI: 10.4103/2141-9248.133474
|View full text |Cite
|
Sign up to set email alerts
|

Do students eventually get to publish their research findings? The case of human immunodeficiency virus/acquired immunodeficiency syndrome research in Cameroon

Abstract: Background:Scientific publication is commonly used to communicate research findings and in most academic/research settings, to evaluate the potential of a researcher and for recruitment and promotion. It has also been said that researchers have the duty to make public, the findings of their research. As a result, researchers are encouraged to share their research findings with the scientific world through peer review publications. In this study, we looked at the characteristics and publication rate of theses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Our finding of a low publication proportion (18%) is corroborated by studies in Cameroon [12], Egypt [9] and India [8] at 14%, 20% and 30%, respectively. Similar studies in higher income countries reported higher but still sub-optimal publication at 40%, 45%, 45%, 65% and 66% in Iran [27], New Zealand [5], Canada [28], Spain [29] and the United States [30], respectively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding of a low publication proportion (18%) is corroborated by studies in Cameroon [12], Egypt [9] and India [8] at 14%, 20% and 30%, respectively. Similar studies in higher income countries reported higher but still sub-optimal publication at 40%, 45%, 45%, 65% and 66% in Iran [27], New Zealand [5], Canada [28], Spain [29] and the United States [30], respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Only two African studies in Cameroon [12] and Zambia [13] documented academic research productivity of post-graduate students in the health sector. Specific to Uganda, existing work on students research has covered either interest and participation of undergraduates in research [14] or mentorship for doctoral candidates [15], but not productivity of their research projects beyond submitting dissertations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies reported the time to publication from completion of theses by post-graduate students. The earliest average time to publication was 2 years (Cameroon, Egypt) [ 14 , 15 ], while the rest were 2.3, 2.8 and 3 years in Uganda [ 13 ], India [ 2 ] and Iran [ 16 ], respectively. Only three studies reported the proportion of abstracts presented in conferences as 54% in Togo, 11% in Cameroon and 2% in Uganda [ 12 – 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The earliest average time to publication was 2 years (Cameroon, Egypt) [ 14 , 15 ], while the rest were 2.3, 2.8 and 3 years in Uganda [ 13 ], India [ 2 ] and Iran [ 16 ], respectively. Only three studies reported the proportion of abstracts presented in conferences as 54% in Togo, 11% in Cameroon and 2% in Uganda [ 12 – 14 ]. Post-graduate students were first authors of their work in 23%, 54%, 62% and 80% in Cameroon, India, Egypt and Turkey, respectively, and in nearly all their papers in Uganda [ 2 , 12 – 14 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation